Noise mapping in Romania within the framework of EU directive 2002/49/EC - POPESCU, Diana Ioana (Archives of Acoustics, 2007)
The demand for environmental noise information in Romania will increase in the near future, first of all due to the integration of the country in the European Union. Some of the European Commission noise directives have already been transposed in Romanian legislation. According with this new legislation, Romania - like the EU countries - has to provide noise maps and also to prepare noise action plans with measures to reduce noise levels when limits are exceeded. The purpose is the definition of a common approach intended to avoid, prevent or reduce the harmful effects of the environmental noise.The paper aims to present the Romanian first experience on noise mapping, during the year 2006, by respecting the requirements of European Directive 2002/49/EC. The general context is described and also specific methods for a practical case study are discussed.